Sources of roughage and milo for finishing steers - Bolsen, K.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Steers fed corn silage gained significantly (P<.05) faster than steers fed any other roughage. Wheat silage ranked second with gains significantly (P<.05) more than gains from milo stover silage, alfalfa hay or corn silage-alfalfa hay combination. Corn silage also produced the most efficient gains, which were significantly (P<.05) more efficient than gains from milo stover silage. Feeding 100% of the grain portion of finishing ratinos as high moisture milo resulted in 13% faster (P<.05) and 13% more efficient (P<.05) gains than feeding equal parts of high moisture milo and dry rolled milo.
What's Ahead for Cattlemen? is known as Cattlemen’s Day, 1977
Keywords: Beef; Roughage; Milo; Steers